2018
DOI: 10.4103/ijo.ijo_488_17
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler imaging of the retrobulbar circulation and plasmatic biomarkers of vascular risk in age-related macular degeneration: A pilot study

Abstract: Purpose:To evaluate preliminarily and compare the level of plasmatic biomarkers of vascular risk in patients with and without exudative age-related macular degeneration (ARMD) and to relate it to vascular resistance alterations in the ophthalmic artery (OA), central retinal artery (CRA), posterior temporal ciliary artery (PTCA), and posterior nasal ciliary artery (PNCA).Methods:Color Doppler imaging of the OA, CRA, PTCA, and PNCA was performed in 30 eyes of 30 cataract patients (control group) as well as in 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Prior studies have shown that CRP increases vascular resistance in the ophthalmic artery in patients with treatment-naïve exudative AMD. 8 Increased levels of monomeric CRP (mCRP), the proinflammatory breakdown product of pentameric CRP, has also been found in the choroidal vessels of donor eyes of patients with AMD. 9 Higher levels of mCRP have also been found in donor eyes of patients with the homozygous Y402H single-nucleotide polymorphism in the gene encoding complement factor H, which has been shown to increase risk for AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that CRP increases vascular resistance in the ophthalmic artery in patients with treatment-naïve exudative AMD. 8 Increased levels of monomeric CRP (mCRP), the proinflammatory breakdown product of pentameric CRP, has also been found in the choroidal vessels of donor eyes of patients with AMD. 9 Higher levels of mCRP have also been found in donor eyes of patients with the homozygous Y402H single-nucleotide polymorphism in the gene encoding complement factor H, which has been shown to increase risk for AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of homocysteine is inversely correlated with retinal vessel diameter and choroidal perfusion and positively correlated with retinal occlusive disease. 66 69 Elevation of homocysteine also causes apoptosis and atrophy of retinal neuronal tissue, particularly the photoreceptors and ganglion cells forming the optic nerve. 70 , 71 Homocysteine is converted to methionine by l -methylfolate and B12, key ingredients of Ocufolin ® ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies suggested its involvement to both neuronal and vascular diseases of the retina such as; central retinal venous [ 31 , 32 ], retinal artery occlusion [ 33 , 34 ], glaucoma [ 35 ], and corneal pathologies and cataracts [ 36 , 37 , 38 ]. Furthermore, elevated Hcy has been suggested as a risk factor and a biomarker for the most common retinal diseases resulting in loss of vision worldwide such as DR [ 39 , 40 , 41 , 42 , 43 , 44 ] and AMD [ 45 , 46 , 47 , 48 ].…”
Section: Hyperhomocysteinemia and Retinal Diseasesmentioning
confidence: 99%